Particulate matter indoors: a strategy to sample and monitor size-selective fractions. Issue 8 (14th September 2022) - Bergmans, Benjamin; Cattaneo, Andrea; Duarte, Regina M. B. O.; Gomes, João F. P.; Saraga, Dikaia; Ródenas García, Mila; Querol, Xavier; Liotta, Leonarda F.; Safell, John; Spinazzé, Andrea; Rovelli, Sabrina; Borghi, Francesca; et al.
Abstract: Particulate matter (PM) is an important player in indoor air quality. Even though PM limit values are in force for more than a decade in Europe and reference methods are well in place for ambient air, measuring indoor PM concentration still remains a challenge and standardizing a measurement protocol is complex. As people stay most of their time indoors, indoor PM is of great interest in terms of public health, as concentration can be drastically different to the one outdoors. This review aims to provide key information to the indoor air monitoring communities, to better understand principal methods suitable for the analysis of indoor PM with their respective main influencing parameters. Advantages and drawbacks of each method are discussed and specific awareness is raised to avoid wrong data interpretation in specific situations. The inter-instrument deviation is also explained and, when possible, methods to correct are proposed.